A new species of Catocala Schrank, 1802 (Lepidoptera: Noctuidae (sensu lato): Erebinae) from Kazakhstan - Saldaitis, Aidas; Kons, Hugo Jr. L.; Borth, Robert J. (Zootaxa, 2014)
Here we describe a new Palearctic species in the noctuid genus Catocala. The new species, C. toropovi sp. n., differs from sympatric and morphologically similar C. repudiata Staudinger, 1888 and C. optima Staudinger, 1888, by wing pattern, male genitalia, and COI 5’ mitochondrial DNA. It is recorded from Kazakhstan, with adults having been collected at ultraviolet lights and baited sugar ropes.